2021
DOI: 10.2147/ijgm.s314911
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Significant Pathway Signaling and Prognostic Value of GNG11 in Ovarian Serous Cystadenocarcinoma

Abstract: Background GNG11 (G protein subunit gamma 11) is a member of guanine nucleotide-binding protein (G protein) gamma family. Few studies elucidated the role of GNG11 in human disease, especially in tumors. The present study initially analyzed the function of GNG11 in ovarian serous cystadenocarcinoma. Methods The differential expression of GNG11 mRNA in ovarian cancer and normal tissues was evaluated through Oncomine, CCLE, Gepia, UCSC Xena and UALCAN databases. The protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The expression of GNG11 mRNA is down-regulated in ovarian cancer patients, and its high expression is associated with poor prognosis (82). GNG11 may play a crucial role in the biological process of ovarian cancer through the ECM-receptor interaction pathway (83).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of GNG11 mRNA is down-regulated in ovarian cancer patients, and its high expression is associated with poor prognosis (82). GNG11 may play a crucial role in the biological process of ovarian cancer through the ECM-receptor interaction pathway (83).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions with between COL5A2, an extracellular matrix protein, and its cell surface receptor promotes transcription of EMT‐related genes via activation of PI3K‐AKT signaling 30 . GNG11 is a member of the guanine nucleotide‐binding protein gamma family and also plays a role in transmembrane signaling; notably, it has been reported to be a predictor of poor prognosis ovarian cancer 31 . MMP2 and MMP9 also promote tumor invasion and metastasis by degrading extracellular matrix proteins and basement membrane 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…A lipid-anchored plasma membrane protein encoded by GNG11 belongs to the G protein gamma family [ 43 ]. One additional study demonstrated that GNG11 contributed to the G-protein Coupled Receptor Protein Signaling in AD [ 44 ].…”
Section: Discussionmentioning
confidence: 99%